Effects of Nicotine Administration and Nicotine Cessation on Bone Histomorphometry and Bone Biomarkers in Sprague–Dawley Male Rats - Hapidin, Hermizi; Othman, Faizah; Soelaiman, Ima-Nirwana; Shuid, Ahmad Nazrun; Mohamed, Norazlina (2011)
Nicotine is a major alkaloid of tobacco, which can increase free radical formation, leading to osteoporosis. The effects of nicotine administration and cessation on bone histomorphometry and biomarkers were studied in 28 Sprague–Dawley male rats. Rats aged 3 months and weighing 250–300 g were divided into four groups: control (C, normal saline for 4 months), nicotine for 2 months (N2), nicotine for 4 months (N4), and nicotine cessation (NC). The NC group was given nicotine for the first 2 months and then allowed to recover for the following 2 months without nicotine. Histomorphometric analysis was done using an image analyzer. ELISA kits were used to measure serum osteocalcin (bone formation marker) and pyridinoline (PYD, bone resorption marker) levels at month 0, month 2, and month 4. All test groups showed a significant decrease in BV/TV, Ob.S/BS, dLS/BS, MAR, BFR/BS, and osteocalcin levels and an increase in sLS/BS and PYD levels compared to group C. No significant differences were observed in all parameters measured among the test groups, except for MAR and BFR/BS. In conclusion, nicotine administration at a dose of 7 mg/kg for 2 and 4 months has detrimental effects on bone metabolism. Nicotine administration at 7 mg/kg for 2 months is sufficient to produce significant effects on bone histomorphometric parameters and biomarkers. In addition, prolonging the treatment for another 2 months did not show any significant differences. Cessation of nicotine for 2 months did not reverse the effects.